2004
DOI: 10.1007/s00122-004-1766-x
|View full text |Cite
|
Sign up to set email alerts
|

The use of microsatellite markers for the detection of genetic similarity among winter bread wheat lines for chromosome�3A

Abstract: Previous studies with chromosome substitution and recombinant inbred chromosome lines identified that chromosome 3A of wheat cv. Wichita contains alleles that influence grain yield, yield components and agronomic performance traits relative to alleles on chromosome 3A of Cheyenne, a cultivar believed to be the founder parent of many Nebraska developed cultivars. This study was carried out to examine the genetic similarity among wheat cultivars based on the variation in chromosome 3A. Forty-eight cultivars, two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 41 publications
2
7
0
Order By: Relevance
“…In Campbell et al (2003), this grain yield QTL detected in the combined analysis explained 28% of the phenotypic variance and the substitution of a WI allele for a CNN allele caused an increase in grain yield. The detection of yield-related QTL in three separate studies in CNN(RICLs3A) (Ali et al, 2011;Campbell et al, 2003;Shah et al, 1999b) and in the current study using WI(RICLs3A) strongly supports the hypothesis that the WI alleles at these clusters of QTLs has (Mahmood et al, 2004) and will likely make an important contribution to grain yield of elite lines of hard winter wheat. Further investigations and additional RICLs are needed to dissect and precisely map the position and expression of Qyld.neb-3A.1 under diff erent fi eld conditions because the ability to detect genetic loci for grain yield is highly infl uenced by genotype, environment, and their interactions.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…In Campbell et al (2003), this grain yield QTL detected in the combined analysis explained 28% of the phenotypic variance and the substitution of a WI allele for a CNN allele caused an increase in grain yield. The detection of yield-related QTL in three separate studies in CNN(RICLs3A) (Ali et al, 2011;Campbell et al, 2003;Shah et al, 1999b) and in the current study using WI(RICLs3A) strongly supports the hypothesis that the WI alleles at these clusters of QTLs has (Mahmood et al, 2004) and will likely make an important contribution to grain yield of elite lines of hard winter wheat. Further investigations and additional RICLs are needed to dissect and precisely map the position and expression of Qyld.neb-3A.1 under diff erent fi eld conditions because the ability to detect genetic loci for grain yield is highly infl uenced by genotype, environment, and their interactions.…”
Section: Discussionsupporting
confidence: 80%
“…Analysis of variance (ANOVA) for AD, PHT, GYLD, GVWT, SPSM, KPS, KPSM, and TKWT was performed separately for each environment using the PROC MIXED procedure (Littell et al, 1996) of SAS version 9.1 (SAS Institute, 2004). In both single location and combined analysis variance components were estimated by considering genotypes, replications, blocks nested within replications, environments, and genotype × environment interaction as random effects.…”
Section: Methodsmentioning
confidence: 99%
“…The number of polymorphic bands per loci ranged from 1 to 3 with an average of 1.6 alleles per locus. Similar type of result were also reported by Dong and Zeng (2003), Ravi et al, (2003), ZhongFu et al, (2003), Mahmood et al, (2004) and Medini et al, (2005 Zeb et al, (2009) and Najaphy et al, (2012). The detected genetic diversity for the six parental genotypes was lower than that of earlier reported by Salem et al, (2008) in wheat genotypes.…”
Section: Resultssupporting
confidence: 86%
“…As a breeder, one would like to believe that if an allele was identified in their germplasm that could significantly increase grain yield that conventional breeding would have found and used the allele. Mahmood et al (2004) using some of the SSR markers used by Campbell et al (2003) and additional SSR markers looked at the molecular diversity of chromosome 3A in historic to modern wheat cultivars adapted to Nebraska. In using the three key polymorphic SSRs between CNN and WI for the main QTL identified by Campbell et al (2003), they found three main clusters of the cultivars.…”
Section: Breaking Chromosomes − What Have We Learned?mentioning
confidence: 99%